Ultra-sensitive SERS detection, rapid selective adsorption and degradation of cationic dyes on multifunctional magnetic metal-organic framework-based composite. (12th May 2020) - Ma, Xiaowei; Liu, Hao; Wen, Sisi; Xie, Qinhui; Li, Linjia; Jin, Jing; Wang, Xiaojun; Zhao, Bing; Song, Wei
Abstract: In-situ and real-time ultra-sensitive monitoring for the degradation process of environmental pollutants is always an important issue of concern to many people. Herein, a multifunctional magnetic metal-organic framework (MOF)-based composite has been successfully constructed and applied in monitoring the disposal of cationic dyes. Owing to its particular MOFs shell and internal gold particles, the composite can be used as an efficient SERS substrate to ultra-sensitively detect the cationic dyes. Furthermore, the prepared MOF-based composite is also a peroxidase-like nanozyme, which can catalytically degrade the adsorbed cationic dyes. Additionally, the magnetic core in the MOF-based composite offers a good magnetic separation capacity, which makes a facile and rapid separation of the catalyst from the reacted solution for recyclability. This work has provided a new way to monitor the catalytic degradation process by SERS technique in the co-existence of catalyst and dye molecules in the reaction system, which can effectively eliminate the absorption of the catalyst compared with the UV–vis technique, showing promising applications in in-situ and real-time pollution disposal monitoring.